Beginning WF Windows Workflow in .NET 4.0 - Collins, Mark J. (Apress, 2012)
When I first started looking at Microsoft’s Workflow Foundation (WF) I had a sense that there was something really useful there, but figuring out the right application of the technology seemed elusive. The available code samples demonstrated some specific features, but there was no roadmap to help bring it all together. So I started writing this book to help others who wanted to understand WF. Along the way, the first beta release of WF 4.0 was made available, which was a complete departure from the previous version. So the first book based on version 3.5 was shelved, and I started writing a new book for WF 4.0. When the second Beta was released with significant changes, the book was once again rewritten. Having watched WF evolve from version 3.5 to 4.0 B1 and then 4.0 B2, and finally 4.0 RC, I can confidently say that these improvements will make your job as a workflow developer much easier.